Microcephaly, characteristic facies, joint abnormalities, and deficient leucocyte chemotaxis: a further case of the syndrome of Say et al - Perandones, Claudia (1996)
Fil: Perandones, Claudia. ANLIS Dr.C.G.Malbrán. Centro Nacional de Genética Médica; Argentina.